IMPROVING STUDENTS’ WRITING ABILITY IN SIMPLE PAST AND PRESENT PERFECT TENSE THROUGH TEACHING STRATEGY OF ERROR RECOGNITION - Mar'atus Sholehah; Supeno Supeno (Universitas Indraprasta PGRI, 2022)
The research was done because more students met difficulties in writing. The objectives of the research are 1. To improve students’ writing ability in simple past tense through teaching strategy of error recognition; 2. To improve students’ writing ability in present perfect tense through teaching strategy of error recognition. The total subject of research is 43 students of two different schools. Techniques of collecting data are test, observation, document, and photograph. The research was in Classroom Action Research with two cycles and each cycle has four steps; planning, acting, observing, and reflecting. The result of analyzing data for students’ ability in simple past tense in cycle I, the “mean” was 60,8. The percentage was 23,37 %. In step II, the “mean” was 78,65 (more than KKM). The percentage of passing was 76,63%. (higher than 75 %). There were improvements from cycle I to cycle II. It is concluded that teaching Strategy of Error recognition in teaching and learning process can improve the students’ ability in writing simple past tense at private senior high school Serang. The result of test score for students’ ability in present perfect tense in step I, the “mean” was 61,35 (less than KKM). The percentage of passing was 23,69 % (less than 75 % minimal mastery level criterion of passing). In step II, the “mean” was 78,25 (more than KKM). The percentage of passing was 76,63 % (higher 75 % minimal mastery level criterion of passing). There were improvements from step I to step II. It is concluded that teaching strategy of error recognition in teaching and learning process can also improve the students’ ability in writing present perfect tense at private senior high school Serang.